Intention to Venture Creation versus Self-Employment: Insights from Intracurricular-Based and Cocurricular-Based University Students - Wijayanti, Cynthia Anna; Johanes, Winty (Proceeding of International Conference on Entrepreneurship (IConEnt), 2023)
Indonesia presently has a low entrepreneurship rate of 1.65%, which falls short of the benchmark for a developed nation. One of the key reasons behind this challenge is the imperative to cultivate tremendous enthusiasm for entrepreneurship among university students. Assessing this interest in entrepreneurship can be accomplished through the Theory of Planned Behavior (TPB), which encompasses components like attitude, subjective norm, and perceived behavioral control. The primary objective of this study is to scrutinize how these three variables influence the intentions of university students majoring in entrepreneurship and students who learn entrepreneurship regarding venture creation (IVC) and self-employment (SE). The sample for this research was chosen using a purposive sampling technique, resulting in 188 valid respondents. The data was subsequently analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the assistance of Smart PLS. This research reveals that attitude significantly impacts students' intentions in both venture creation and self-employment. While subjective norm does not affect students' inclination toward venture creation, it does influence their interest in pursuing self-employment. Finally, perceived behavioral control shapes students' tendencies toward venture creation but does not influence their intentions for self-employment.